Perubahan Parsial di Lembaga Pendidikan Islam - Huda, Muh. Nurul (Institut Agama Islam Negeri (IAIN) Tulungagung, 2014)
Partial changes are usually caused by the inability of an institution or organization Islamic education to overcome the resistance changes. Resistance can occur in form of individual resistance and organizational resistance. Partial change will not result in an increase in the quality of education aspired. However, partial changes will cause a potential conflict, the so called as latent conflicts that are difficult to be solved. Partial change also will not yield better work and increased motivation even it lead to better cooperation.